Alternating Array Stacking of Ag26Au and Ag24Au Nanoclusters. Issue 29 (21st June 2019) - He, Lizhong; Gan, Zibao; Xia, Nan; Liao, Lingwen; Wu, Zhikun
Abstract: An assembly strategy for metal nanoclusters using electrostatic interactions with weak interactions, such as C−H⋅⋅⋅π and π⋅⋅⋅π interactions in which cationic [Ag26 Au(2‐EBT)18 (PPh3 )6 ] + and anionic [Ag24 Au(2‐EBT)18 ] − nanoclusters gather and assemble in an unusual alternating array stacking structure is presented. [Ag26 Au(2‐EBT)18 (PPh3 )6 ] + [Ag24 Au(2‐EBT)18 ] − is a new compound type, a double nanocluster ion compound (DNIC). A single nanocluster ion compound (SNIC) [PPh4 ] + [Ag24 Au(2‐EBT)18 ] − was also synthesized, having a k‐vector‐differential crystallographic arrangement. [PPh4 ] + [Ag24 Au(2, 4‐DMBT)18 ] − adopts a different assembly mode from both [Ag26 Au(2‐EBT)18 (PPh3 )6 ] + [Ag24 Au(2‐EBT)18 ] − and [PPh4 ] + [Ag24 Au(2‐EBT)18 ] − . Thus, the striking packing differences of [Ag26 Au(2‐EBT)18 (PPh3 )6 ] + [Ag24 Au(2‐EBT)18 ] −, [PPh4 ] + [Ag24 Au(2‐EBT)18 ] − and the existing [PPh4 ] + [Ag24 Au(2, 4‐DMBT)18 ] − from each other indicate the notable influence of ligands and counterions on the self‐assembly of nanoclusters. Abstract : A double nanocluster ion compound (DNIC) was synthesized that has a unique alternating stacking array of the cationic and anionic nanoclusters. A single nanocluster ion compound (SNIC), exhibiting a k‐vector‐differential crystallographic arrangement, was also obtained. The notable packing differences among the DNIC and the new and the existing SNICs indicate the dramatic influence of ligands and counterions on crystallographic arrangement.